The assessment of patients with non-erosive gastroesophageal reflux disease by using the Bravo® pH monitoring system - Gök Mehmet; Gencdal Genco (Sanamed, 2022)
Background and aim: Gastroesophageal reflux disease (GERD) is a common disease in the world. GERD is always treated with drugs. The Bravo® wireless pH monitoring system is a good technique. The Bravo® may affect increasing the specificity and sensitivity in the diagnosis of GERD with its 48-hour recording feature. In this study, we aimed to assess the diagnostic performance of the Bravo® pH monitoring system in patients with non-erosive GERD.